The impact of administrative empowerment on the quality of banking service; An applied study on Al-Rajhi Bank - Abha – KSA; year 2020-2021 - Ali, Muram Ahmed (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aims to know the extent to which the institution applies the activities related to the presence of administrative empowerment and its impact on the level of quality of banking services in it, according to the descriptive analytical approach. Due to the small size of the study population, the comprehensive survey method was applied, and to achieve this, the researcher designed a questionnaire as a tool for collecting information. The study was conducted on (80) questionnaires, (77) questionnaires were adopted by (96%), and the data were analyzed using the program (Spss), where a number of statistical methods were used to verify the validity of the hypothesis. The study reached several results, most notably: There is a statistically significant relationship between administrative empowerment and the quality of banking service at a lower morale level (0.05). The study recommended the need for the bank’s management to believe in the capabilities of employees and to trust them by giving them sufficient authority to act on issues related to their work because of its importance in raising the atmosphere of trust and cooperation within the framework of their departments, which leads to raising the efficiency and effectiveness of performance.
Keywords: administrative empowerment; quality; service; quality of banking service